Plasma indoleamine 2,3-dioxygenase activity, a potential biomarker for tuberculosis - Adu-Gyamfi, Clement (My University, 2016)
Tuberculosis (TB) is a major global health challenge, especially in high HIV prevalence settings. To date, however, there is no validated biomarker for diagnosing TB in HIV infected patients. Indoleamine 2, 3 dioxygenase (IDO) is an immunoregulatory enzyme capable of modulating cell mediated immunity (CMI). IDO catalyses the breakdown of tryptophan (Trp) to its toxic metabolites collectively known as kynurenines (Kyn). Elevated IDO activity has been proposed as a prognostic biomarker for TB, however, there is no longitudinal data to assess the clinical significance of elevated IDO activity in HIV-TB co-infection. We investigated whether IDO activity, as measured by Kyn-to-Trp ratio, using ultra-performance liquid chromatography mass spectrometry (UPLC-MS/MS) can act as a biomarker for diagnosing TB in HIV infected patients who develop active TB disease. Methodology Kyn and Trp concentrations were measured simultaneously using UPLC-MS/MS in the plasma of 32 HIV infected patients who developed active TB during a longitudinal study and compared with 70 control subjects, age and CD4 cell count matched, in the same HIV infected cohort who did not develop TB. Results IDO activity was significantly higher in TB patients than controls at the time of TB diagnosis (P = 0.0001). At 6 months prior to TB diagnosis, IDO activity was significantly higher in those who developed TB than controls (P = 0.0001). Within 6 months of anti-TB treatment, IDO activity in TB patients declined to almost same levels as that of the controls. To evaluate diagnostic significance of IDO activity using a receiver operating characteristic (ROC) curve, we selected 0.70 as the optimal cut-off. At time of TB diagnosis using both laboratory confirmed and clinical TB as gold standard, IDO activity gave a diagnostic sensitivity of 100% and a specificity of 98.5% with Positive and Negative predictive values of 96.9% and 100% for detecting active TB cases. Conclusion Our results, demonstrate the plausibility of increased IDO activity as a biomarker of active TB in HIV positive patients. Further, IDO activity may be a useful biomarker for predicting progress to active TB disease within 6 months or monitoring response to TB treatment. Strengths of the study include inclusion of an HIV infected control group and a longitudinal study design.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science Medicine Johannesburg, 2016
Keywords: Plasma indoleamine 2,3-dioxygenase; Tuberculosis